294 Effect of Supplementing Rumen-protected Methionine on Production, Apparent Digestibility and Economic Effectiveness in Lactating Holstein Dairy Cows. (8th October 2021) - Wei, Jialin; Cao, Zhijun; Li, Yuanxiao
Abstract: The aim of the present study was to evaluate the effects of reducing dietary crude protein (CP) levels and supplementing rumen-protected methionine (RPM) on production, apparent digestibility of nutrients and economic effectiveness of lactating Holstein cows. A total of 96 (60 ± 7 d in milk; 34.39 ± 5.74 kg/d of milk production; mean ± SD) lactating Holstein dairy cows were randomly assigned to 1 of 2 treatments: diet containing 17.3% CP without RPM (control group; CON); diet containing 16.4% CP with supplementing 15.0 g/d of RPM (treatment group; RPM). All the data were analyzed using one-way analysis of variance (ANOVA) of SAS (SAS version 9.2, SAS Institute Inc., Cary, NC.). No effects were observed of reducing dietary CP on somatic cell counts, milk yield and milk composition including fat, protein, lactose, total solid, solids-not-fat and milk urea nitrogen. The total apparent digestibility of nutrients was similar between treatments, while RPM group had higher calcium digestion (44.24% vs. 42.75% ± 10.13%) and phosphorus digestion (48.50% vs. 45.96% ± 12.90%) numerically. In addition, supplying the diet of 16.4% CP with RPM supplementation to cows could reduce feeding cost by 0.5 $/d per cow and boost net profits. In conclusion, lower dietary CP with RPM supplementation did not limit milk yield, milk composition and apparent digestibility of nutrients, and also could improve the economic benefits of the dairy farms.